Potential impacts of hard infrastructure development on agricultural trade - Al-Maamari, Aaisha, author; Countryman, Amanda, advisor; Thilmany, Dawn, committee member; Pena, Anita, committee member (Colorado State University. Libraries, 2017)
The development of hard infrastructure has the potential to enhance agricultural production and international agricultural trade. Good quality physical networks could reduce the transport costs for producers and suppliers, thereby increasing the volume of agricultural bilateral trade. For most countries, tariff rates, transport costs, geographic drawbacks, and other nontariff barriers are considered to be the most significant potential impediments to trade. This study estimates the role of hard infrastructure on agricultural bilateral trade among North and Latin American countries, as one determinant of transport costs. By using panel data for agricultural imports from 2006 to 2014, we measure the potential impact of the quality of overall hard infrastructure as well as specific modes of transport networks such as roads, railroads, ports and airports infrastructure on the prevalence and patterns of agricultural trade. A modified gravity model of trade has been used to measure the impact of different trade barriers on the trade of food, animal, vegetable and aggregated agricultural products. Results show that the distance between countries and hard infrastructure are statistically significant and play an important role in determining transport costs as well as the variation in agricultural bilateral trade. For both aggregated and disaggregated agricultural trade, the estimated coefficients show that exporters' infrastructure has a larger impact on trade than importers' infrastructure. Results show that a 10 percent improvement in the quality of an exporters' hard infrastructure may increase total agricultural import volume by 8.6 percent, while a 10 percent improvement in importers' hard infrastructure may increase aggregated agricultural imports by 6.0 percent.
Keywords: airports; ports; roads; hard infrastructure; agricultural trade; railroads